(3fXe GdBLQhejIs - (3TQa GdOjf jMji Hf fhQGdOjf ehSi Hf QeVGf GdYeQjWjs; (3GHf GLQhe , CHh YHO Gddg eMeO Hf eMeO Hf OGhO GdUfgGLj,J (B723 (3g` s ((3YHOGdSdGe Hf YHOGdSdGe Hf Ydj GdeZQHj GdJhfSj GdMfaj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj bO habfG ddYde NjQ Ndbg hddJbi s
(3BNQgG (B:s
(3bO Je fXe gPg GdebOeI aj QHY Cda cGajkG ef CMceg fXe GdabjQ GdTQja GdYeQjWj Pj GdYLR hGdJbUjQ hGdJaQjW hGab GdaQGZ s
(3HgG fXGe GdJYbjHIs
(3Jhai GdeDda HYO (B989(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B215s
Keywords: (3GdfMhs